Drug Targets in Kinetoplastid Parasites - Majumder, Hemanta K.; SpringerLink (Online service) (New York, NY : Springer New York, 2008)
If viewed globally, the parasitic diseases pose an increasing threat to human health and welfare. The diseases caused by kinetoplastid protozoan parasites like Leishmania and Trypanosoma continue as a cause of suffering for many millions of people in both tropical and subtropical regions of the world. Leishmania species are found throughout Latin America, Africa and Asia. Trypanosoma cruzi that cause Chagas' disease is endemic in Latin America, while members of Trypanosoma brucei group are found in sub-Saharan Africa. Although the past two decades has witnessed commendable research efforts and technical advances in our understanding of the biochemistry, molecular and cell biology of these pathogens, the dreaded protozoal diseases caused by these organisms threaten mankind. Therapeutic tools for the treatment of most parasitic diseases are extremely limited. The development of parasites resistant to many of the available drugs is also responsible for the depressing picture of disease persistence and death. Development of commercially available vaccines is still far from reality, though research and trial programs continue.
Arsenite Resistance in Leishmania and Possible Drug Targets -- Unique Characteristics of the Kinetoplast DNA Replication Machinery Provide Potential Drug Targets in Trypanosomatids -- Drugs and Transporters in Kinetoplastid Protozoa -- Selective Lead Compounds against Kinetoplastid Tubulin -- Fishing for Anti-Leishmania Drugs: Principles and Problems -- Sterol 14-Demethylase Inhibitors for Trypanosoma cruzi Infections -- Histone Deacetylases -- Targeting Glycoproteins or Glycolipids and Their Metabolic Pathways for Antiparasite Therapy -- DNA Topoisomerases of Leishmania: The Potential Targets for Anti-Leishmanial Therapy -- Antiparasitic Chemotherapy: -- Searching the Tritryp Genomes for Drug Targets -- Purine and Pyrimidine Metabolism in Leishmania.
Keywords: MEDICINE; MEDICAL PARASITOLOGY; BIOMEDICINE; PARASITOLOGY